Lydhør identitetsstøtte i samtaler med personer med demens: En studie av intervjuer i en femårig narrativ forløpsstudie - Thorsen, Kirsten; Johannessen, Aud (Nordisk tidsskrift for helseforskning, 2020)
Responsive identity support in conversations with people with dementia: A study of interviews in a five-years narrative longitudinal study A narrative longitudinal study depends on trust and a positive relationship between the interviewer and the participant to encourage the participant’s continued participation. In reported studies, the methodological part is usually too short to present the complexities in dialogues over time. We therefore have analyzed the interview processes with younger people with dementia, relating the interactions to central concepts associated with identity. The aim was to explore the methodological interview approach used in a longitudinal study, focusing on supporting identity and self-esteem. We used the concept of responsive identity to illuminate our findings. In addition, we demonstrate how the interview dialogues can support identity and self-esteem of the participants. The core of this approach is that the interviewee, living with dementia, should be seen, confirmed and supported to preserve the person`s self and dignity. Dialogue with responsive identity support is a fruitful research method in dementia research. This approach can be generalized to person-centred communication in health and caring relationships.